The rpoE gene of Escherichia coli, which encodes sigma E, is essential for bacterial growth at high temperature. - Hiratsu, K (1995)
In vitro transcription analysis has shown that only RNA polymerase containing an alternative sigma subunit, sigma E, activates transcription from one of the rpoH promoters and the htrA promoter. The location of the rpoE gene encoding sigma E on the Escherichia coli chromosome has recently been established, but no rpoE mutant has yet become available for phenotypic testing. We cloned the rpoE gene from the lambda-ordered clones of the E. coli genome and confirmed that the reconstituted RNA polymerase containing the gene product (E sigma E) can transcribe htrA in vitro. We constructed an rpoE-defective strain by gene disruption using the cloned rpoE gene. We demonstrate that expression of htrA is completely dependent on the rpoE gene in vivo and that the rpoE gene is essential for bacterial growth at high temperature.